Co-visualization of DNA damage and ion traversals in live mammalian cells using a fluorescent nuclear track detector - Kodaira, Satoshi (J Radiat Res, 2015)
The geometric locations of ion traversals in mammalian cells constitute important information in the study of heavy ion-induced biological effect. Single ion traversal through a cellular nucleus produces complex and massive DNA damage at a nanometer level, leading to cell inactivation, mutations and transformation. We present a novel approach that uses a fluorescent nuclear track detector (FNTD) for the simultaneous detection of the geometrical images of ion traversals and DNA damage in single cells using confocal microscopy. HT1080 or HT1080–53BP1-GFP cells were cultured on the surface of a FNTD and exposed to 5.1-MeV/n neon ions. The positions of the ion traversals were obtained as fluorescent images of a FNTD. Localized DNA damage in cells was identified as fluorescent spots of γ-H2AX or 53BP1-GFP. These track images and images of damaged DNA were obtained in a short time using a confocal laser scanning microscope. The geometrical distribution of DNA damage indicated by fluorescent γ-H2AX spots in fixed cells or fluorescent 53BP1-GFP spots in living cells was found to correlate well with the distribution of the ion traversals. This method will be useful for evaluating the number of ion hits on individual cells, not only for micro-beam but also for random-beam experiments.